Brand and Strategy of Branding of the Croatian Armed Forces in the Context of Psychological Combat Readiness and the Art of War - Marina Svrze; Dina Žižić; Mijo Knezović (Strategos, 2021)
The aim of the research in the first theoretical section is to throw light on and identify the link between Psychological Combat Readiness (NATO’s Morale and Unit Effectiveness), perception, brand and branding in the context of the art of war. Through theoretical elaboration of relevant authors and examples from the history, the link between the stated terms has been identified as well as their importance in the context of the human factor – Psychological Combat Readiness in armed conflicts. In the second empirical section the research results validate the quality of the Croatian Armed Forces within the context of a brand as well as public perception and high regard for the CAF in that context. However, the results of the research point towards the need for further development through two synchronised development directions: the development of the brand identity and communication strategy aimed at improvement of the public perception of the brand, with the goal of maintaining and developing the power of the state and ensuring competitiveness in current security and defence environment.